The Development of Mucosal Immunization as an Alternative Approach for Production of Antisera Against Saw Scale Viper from Sindh: Production of Antisera - Ahmed, Zameer; Zameer, Sambreen; Sharafat, Shaheen; Khanani, Muhammad Rafiq (Biological Sciences - PJSIR, 2021)
The reported cases of snake bite are 5.4 million per year, making the serious envenoming issue so, that WHO categorises cases of snake bite in neglected tropical diseases. Anti snake venom is produced by intramuscular injection of crude venom with different formulation of adjuvants to equine animals, but these intramuscular injections have several serious health impact in equine. Snake species categorised according to geographical locations, and there is a different composition of the snake venom at different locations. So, this research had been designed and evaluated new oral adjuvant formulation for viper family of Sindh, Pakistan. This is a animal immune based analysis consisting two Saw scale viper from Thar and costal area of Sindh because both have different habitat and morphological appearance. The venom toxin protein, combined with a mineral oil adjuvant for oral immunization. The adjuvant with venom via oral route produced of specific IgG and horse give maximum response with three doses of venom. The antibody titer was measured by ELISA showed significant results in both groups. For confirmation of specific antibodies isolated from horse serum, serum neutalization assay and immunodiffusion test were carried out. The snake venom with oral adjuvant immunization, is safe, efficient and time saving for production of equine Immunoglobulins IgG.